Ethnographic Insights into Winedocking: Bridging Wine Tourism, Producers, and Travelers for Immersive Experiences - Bousquet, Julien (Journal of Modern Hospitality, 2025)
This article examines winedocking, an innovative blend of wine tourism and boondocking, where travelers camp overnight at vineyard properties. Using ethnographic methods, it explores the behaviors and motivations of winedockers and producers, revealing how this practice enhances visitor experiences and economic opportunities for wineries. Winedocking appeals to modern travelers seeking sustainability, authenticity, and adventure. Travelers enjoy immersive connections with winemakers, while producers benefit from additional revenue and visibility. Fieldwork across U.S. wine regions, including interviews with 47 travelers and 12 winery owners, highlights the mutual benefits and challenges of this trend. The study situates winedocking within the broader wine tourism landscape, demonstrating its potential to drive sustainable tourism and innovation in the industry. It provides insights for producers and stakeholders, emphasizing winedocking’s role in meeting evolving consumer preferences and supporting local economies.